ANALISIS PENGARUH PENGANGGURAN DAN EKSPOR TERHADAP PDRB HARGA KONSTAN (SUMATRA UTARA 2006-2019) - Harfensius Turnip (Universitas Negeri Medan, 2021)
This study aims to analyze and explain the effect of unemployment on gross domestic product (GDP) at constant prices and the effect of exports on gross domestic product (GDP) at constant prices. This study uses secondary data from panel data from North Sumatra BPS data, where the authors limit the research time from 2006-2018. The data processing in the research carried out is by using the eviews application. The results of this study indicate that: Unemployment variable has a negative effect on Constant Price GRDP in North Sumatra Province, Export variable has a positive effect on Constant Price GRDP in North Sumatra Province and the independent variable (unemployment, eskpro) has a significant influence on the dependent variable (Constant Price GRDP). North Sumatra Province)._____________________________________________________Keywords: Exports, Unemployment and GDP at Constant Prices